Tidal resource characterization in the Folda Fjord, Norway. (April 2016) - Carpman, Nicole; Thomas, Karin
Highlights: Tidal current measurements have been performed at a prospective tidal energy site. Characterizing metrics have been calculated. A simple model to predict peak current speeds from tidal chart data is proposed. Abstract: For tidal-stream energy industry to be fully realized, lower velocity sites and fjords should be developed. Finding new prospective sites for in-stream energy extraction from tidal currents is an area of ongoing research. In this paper, the tidal flow at a fjord inlet has been characterized using acoustic Doppler current profiler (ADCP) measurements. This work is based on two survey measurement techniques: transect measurements to map the spatial variability, and seabed measurements to map the temporal variability. The data was analyzed in terms of characterizing metrics, to ensure they are comparable with other resource assessments. Results show that currents exceed 1 m/s for 38% of the time with peak currents of 2.06 m/s at hub height (middle of the water column) and the directional asymmetry is less than 1° between ebb and flood, indicating a truly bi-directional flow. A simple prediction model is proposed which allows peak current speeds to be accurately predicted in the channel center from tidal range data using a linear relationship. The relationship is shown to be strong, with a correlation coefficient of 0.98 at hub height, and a standard variation typically less than 10 cm/s. Furthermore, it is show that a minimum of 9 days of measurements are required to set up the model, although it takes 29 days to reduce the error in peak speed to less than 1%. However, the error is expected to vary depending on where in the monthly tidal cycle the survey begins, it is thus recommended to measure around spring tide if the measurement period is short.